Sustainability and resilience in building design: Discussion on two case studies - Licia Felicioni; Antonín Lupíšek; Jacopo Gaspari; Ernesto Antonini (Acta Polytechnica CTU Proceedings, 2022)
Designing sustainable and, at the same moment, resilient buildings is a necessity to reach the UN Sustainable Development Goals by 2030. However, these two building design approaches - sustainability and resilience - are usually treated separately. Typically, resilience-improving strategies are placed only after a disruptive event and not at the design stage. It is clear that there is a substantial intersection between sustainability and resilience and this manuscript aims to determine more precisely the commonalities and contradictions seen in building design sustainable and resilient approaches as crucial elements for improving their cooperation in buildings. To accomplish this, the authors qualitatively analysed two case studies - respectively claiming to be sustainable and resilient - to understand if a sustainable building can also be considered resilient and vice versa. This paper is addressed to the private and public sectors that have a decisive role in building design and are determined to take tangible steps to influence decision-making and resilience-based solutions already at the design phase. In conclusion, once the commonalities of resilience and sustainability are highlighted, a building designed as sustainable or resilient will be in line with both long-term perspectives.